Kualitas Produk, Persepsi Harga, Citra Merek dan Promosi terhadap Proses Keputusan Pembelian (Studi Pada Banaran 9 Coffee and Tea di Gemawang, Kabupaten Semarang) - Rizky Syamsidar; Euis Soliha (Jurnal Bisnis dan Ekonomi, 2019)
This study examines the effect of product quality, price perception, brand image, and promotion on the purchasing decision process. This research is conducted in Banaran 9 Coffee & Tea, Gemawang, Semarang Regency. The sampling method uses the purposive sampling and the data collection uses a questionnaire. The research is done from 2017 to 2019. Relations and / or influence between variables are explained using multiple regression analysis methods. The results show that the perception of price and promotion have a positive and significant influence on the process of purchasing decisions, while product quality and brand image do not significantly influence the process of purchasing decisions